2015
DOI: 10.1007/s00246-015-1303-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Dilation and Right Ventricular Function in Acute Kawasaki Disease

Abstract: Coronary artery inflammation and aneurysm formation are the most common complications of Kawasaki disease (KD). Valvulitis and myocarditis are also well described and may lead to valvar regurgitation and left ventricular dysfunction. However, functional changes in the right heart have rarely been reported. We noted several acute KD patients with dilated pulmonary arteries (PA) and thus sought to systematically characterize PA size and right-heart function in an unselected cohort of KD patients cared for at a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Clinically, LV dysfunction presumably related to myocardial inflammation has been described in series of patients with “KD shock syndrome.” One case report showed findings of myocardial edema and decreased LV function by cardiac magnetic resonance imaging . Numano et al reported the existence of RV dysfunction in acute KD documented by echocardiography . Therefore, myocardial inflammation in both the right and left heart in acute KD may lead to dispersion of ventricular repolarization and bifid T waves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, LV dysfunction presumably related to myocardial inflammation has been described in series of patients with “KD shock syndrome.” One case report showed findings of myocardial edema and decreased LV function by cardiac magnetic resonance imaging . Numano et al reported the existence of RV dysfunction in acute KD documented by echocardiography . Therefore, myocardial inflammation in both the right and left heart in acute KD may lead to dispersion of ventricular repolarization and bifid T waves.…”
Section: Discussionmentioning
confidence: 99%
“…2,25,26 Clinically, LV dysfunction presumably related to myocardial inflammation has been described in series of patients with "KD shock syndrome." 29 Therefore, myocardial inflammation in both the right and left heart in acute KD may lead to dispersion of ventricular repolarization and bifid T waves. 28 Numano et al reported the existence of RV dysfunction in acute KD documented by echocardiography.…”
Section: Generation Of Bifid T Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). Using the mean diameters of MPA and AAO of control subjects as a contrast standard, the DSCT-based diameters of both arteries in patients were compared with the control values: MPA stenosis was defined as <75% contrast standard 3 , 23 and MPA dilation was defined as Z-score (standard deviation units from the mean) >2 24 . AAO dilation and stenosis were regarded as Z-score > 2 and Z-score < −2, respectively 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Notably, pulmonary arterial hypertension (PAH), pulmonary artery dilation, pulmonary artery aneurysms, and right ventricle (RV) dysfunction have been observed in patients with KD (Briceno-Medina et al, 2016;Escalon et al, 2018;Nicholson et al, 2013;Ugi et al, 2010). Furthermore, a remarkably lower pulmonary arterial compliance and diffused histologic changes in pulmonary arteries are also observed in patients with KD (Masuda et al, 1986;Numano et al, 2016;Sugimoto et al, 2012;Takahashi K., 2017). However, the underlying mechanisms responsible for these pulmonary arterial abnormalities in KD are still unknown and need further investigation.…”
Section: Introductionmentioning
confidence: 99%